Transformasi Nilai-Nilai Islam ke dalam Sistem Manajemen Pondok Pesantren Modern Al-Musyarrofah - Ilham Nugraha; Rohmat Mulyana Sapdi; Irawan (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
The transformation of Islamic values ​​into the management system of modern Islamic boarding schools (pesantren) is a crucial issue because Islamic boarding schools are required to maintain their Islamic identity while simultaneously fulfilling the need for effective, transparent, and adaptive educational governance. Previous studies generally discuss Islamic boarding school modernization, character building, or educational quality, but have not specifically explained how Islamic values ​​are translated into the structure of policies, administration, learning, student development, and the institution's work culture. This study focuses on how the values ​​of trustworthiness, sincerity, discipline, deliberation, responsibility, courtesy, and exemplary behavior are transformed into the management system of the Al-Musyarrofah Modern Islamic Boarding School. The study used a qualitative approach with a case study design at the Al-Musyarrofah Modern Islamic Boarding School. Data were collected through interviews with foundation administrators, boarding school leaders, teachers, administrators, students, and alumni, as well as through observations of Islamic boarding school activities and documentation studies of rules and regulations, activity schedules, development records, and administrative documents. Data were analyzed through data reduction, data presentation, triangulation, and conclusion drawing. The research findings indicate that the transformation of Islamic values ​​occurs through the institutionalization of values ​​into policies, daily practices, teacher role models, institutional deliberations, and administrative services. This study recommends strengthening value evaluation indicators and expanding the study to other Islamic boarding schools so that the values-based management model can be tested more comparatively